Ijtihad: a reflection on its role and scope - Ali, Mohd Mumtaz (International Islamic University Malaysia, 2011)
It is generally claimed that some of the outstanding features of modern age are the ‘rule of law’ and the emergence of ‘civil society’. In spite of supposedly civil and caring societies, millions of people around the world are still suffering from diseases, crimes and injustice. On the global political scene, "might is right" prevails; more weapons are being produced than rice and wheat. Sense of insecurity and violence is dominating everywhere. To overcome this phenomenon, some analysts are suggesting a need for strong link between law and social obligations, and some others are emphasizing the need to integrate moral and ethical values into the sociopolitical sphere of our lives. However, our contention is that all these measures have proven superficial. The predicament of modern societies cannot be alleviated unless and until a strong relationship in between law, social obligations and ijtihad is established and practiced in all spears of life. In this paper, it is argued that the real cause of contemporary malaise lies in the absence of ijtihad. Ijtihad is either neglected or restricted to certain legal dimensions. This paper contends that only the application of ijtihad as the main methodology of thought and action would enhance consciousness of social obligations of individuals, policy makers, scientists, and political authorities, and would guarantee real civilizational development. Hence, ijtihad should be taken as the methodology of development and civilization.